1995
DOI: 10.1103/physrevb.51.840
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of phases and microstructure inFe81B13.5

Abstract: A comparative study of electron-beam and pulsed-laser irradiation effects in metallic glasses has been performed in order to understand the relationship between magnetic behavior and select variations in the structural characteristics of alloy phases. Samples of FegiB, 3 5Si3 5C2 metallic glass were irradiated with a pulsed excimer laser (A, = 308 nm,~= 10 ns), with a high-energy electron beam ( 8 = 7 MeV), and with low-energy electron beams (8'=30 and 50 keV). Irradiation-driven changes in the magnetic anisot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…[5][6][7][8]. This behavior is consistent with some previous findings [1][2][3][4]. Indeed, it follows that the in-plane compressive stresses associated with the laser irradiation have caused atomic spins to rotate in a direction normal to the sample surface.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…[5][6][7][8]. This behavior is consistent with some previous findings [1][2][3][4]. Indeed, it follows that the in-plane compressive stresses associated with the laser irradiation have caused atomic spins to rotate in a direction normal to the sample surface.…”
Section: Discussionsupporting
confidence: 88%
“…Consequently, the calculated values of the magnetic texture parameter R 21 (see also Fig. 9) show that the magnetic moments of the as-prepared material are preferentially oriented in the plane of the ribbon sample, as observed for other amorphous alloys with similar compositions [1][2][3][4]. Fig.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In order to assess the long-term stability of radwaste forms, a number of investigations have focused on the radiation tolerance, and showed that irradiation induced the phase segregation in alloys and glass [8][9][10]. 90 Sr is a highly radiotoxic fission product, the decay of the strontium emit beta particles with energy E 0.546 and 2.28 MeV.…”
Section: Introductionmentioning
confidence: 99%